Nephrogenic adenoma in a female urethral diverticulum: Clinical presentation and surgical management - Leanne Brechtel; Veena Venkatesh; Nathanael Christensen; Stephanie Stauffer; Annah Vollstedt (Journal of Case Reports and Images in Urology, 2026)
Introduction: Nephrogenic adenoma is a benign lesion of the urinary tract that is rarely found within a urethral diverticulum. The nonspecific symptoms of urethral diverticula can often lead to delayed or missed diagnosis, complicating management. Case Report: We present the case of a woman who presented with vaginal discomfort and was ultimately found to have a periurethral mass. Pelvic magnetic resonance imaging (MRI) confirmed the presence of a periurethral mass. Definitive surgical excision and histopathological analysis confirmed the presence of nephrogenic adenoma within the urethral diverticulum. Postoperatively, the patient did well with near resolution of her symptoms. Conclusion: This case highlights the importance of a broad differential diagnosis, the utility of advanced imaging, and relying on histopathology to distinguish between benign and malignant lesions. For nephrogenic adenoma, surgical excision remains the optimal treatment, often offering excellent outcomes.